Use of CuNi/YSZ and CuNi/SDC Catalysts for the Reverse Water Gas Shift Reaction. (17th February 2015) - Lortie, Maxime; Isaifan, Rima J.
Abstract : Cu50 Ni50 nanoparticles were synthesized using a modified polyol method and deposited on samarium-doped ceria, SDC, and yttria-stabilized zirconia, YSZ, supports to form reverse water-gas shift, RWGS, catalysts. The best CO yields, obtained with the Cu50 Ni50 /SDC catalyst, were about 90% of the equilibrium CO yields. In contrast CO yields using Pt/SDC catalysts were equal to equilibrium CO yields at 700°C. Catalyst selectivity to CO was 100% at hydrogen partial pressures equal to CO2 partial pressures, 1 kPa, and decreased as methane was formed when the hydrogen partial pressure was 2 kPa or greater. The reaction results were explained using a combination of Eley-Rideal and Langmuir-Hinshelwood mechanisms that involved adsorption on the metal surface and the concentration of oxygen vacancies in the support. Finally the Cu50 Ni50 /SDC catalyst was found to be thermally stable for 48 hours at 600/700°C.